2019
DOI: 10.1002/mabi.201900033
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Interactions of Polyamide Based Sequence‐Controlled Glycomacromolecules with Concanavalin A

Abstract: Binding of mannose presenting macromolecules to the protein receptor concanavalin A (ConA) is investigated by means of single‐molecule atomic force spectroscopy (SMFS) in combination with dynamic light scattering and molecular modeling. Oligomeric (Mw ≈ 1.5–2.5 kDa) and polymeric (Mw ≈ 22–30 kDa) glycomacromolecules with controlled number and positioning of mannose units along the scaffolds accessible by combining solid phase synthesis and thiol–ene coupling are used as model systems to assess the molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…On the other hand, Ratto et al showed via single molecule AFM that the dissociation of the four ConA binding sites from a dense layer of mannose resulted in less than additive contribution from each binding site, that is, negatively cooperative multivalency . Our single molecule atomic force microscopy studies (SM‐AFM) on sequence defined glycomacromolecules (Figure ) confirmed that linear structure can simultaneously bind to multiple receptor sites; however, stretching of the ligands in contact with the carbohydrate binding protein to accommodate more binding sites was not observed . In addition, large and highly multivalent glycomacromolecules capable of clustering multiple receptors actually showed a reduced binding propensity, owing to their flexibility and steric repulsion .…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 62%
See 2 more Smart Citations
“…On the other hand, Ratto et al showed via single molecule AFM that the dissociation of the four ConA binding sites from a dense layer of mannose resulted in less than additive contribution from each binding site, that is, negatively cooperative multivalency . Our single molecule atomic force microscopy studies (SM‐AFM) on sequence defined glycomacromolecules (Figure ) confirmed that linear structure can simultaneously bind to multiple receptor sites; however, stretching of the ligands in contact with the carbohydrate binding protein to accommodate more binding sites was not observed . In addition, large and highly multivalent glycomacromolecules capable of clustering multiple receptors actually showed a reduced binding propensity, owing to their flexibility and steric repulsion .…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 62%
“…Other direct binding assays using various scaffolds such as dendrimers [48] or nanoparticles [49] as scaffolds also mainly showed additive effects due to the multivalent presentation of carbohydrates, but not positively cooperative interactions due to chelate-like binding or subsite binding to the receptor. To shed more light on the molecular mechanisms of carbohydrate binding X-ray crystallography, [50][51][52][53] or single molecule techniques based on labeled carbohydrates for NMR spectroscopy [54] and single molecule AFM [55][56][57][58][59][60] were used. For example, Drescher and coworkers showed that flexible PEG-based ligand scaffolds can stretch to accommodate an additional binding site after binding to a first site at a carbohydrate binding protein.…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47,48 ] To form stable ConA coatings, we used epoxy functionalized glass slides as described previously. [ 27 ] All preparation steps were done at pH 7.4, where ConA attains a tetrameric structure with four mannose binding sites at a minimum spacing of 7.2 nm. The tetrameric structure ensures that each ConA molecule at the glass surface has binding sites facing the solution and are available for binding.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4,20,21 ] The factors that may increase the binding affinities upon temperature increase are: 1) an increase of carbohydrate subunit density due to an increase of statistical rebinding or subsite binding. [ 25–27 ] 2) An increase of carbohydrate surface density due to the formation of a compact polymer globule where the hydrophilic carbohydrates enrich at the surface. [ 28 ] 3) A smoother surface upon polymer collapse leading to a reduced steric repulsion.…”
Section: Introductionmentioning
confidence: 99%